Evaluating the role of Neutrophil-to-Lymphocyte and Platelet-to Lymphocyte Ratios as Biomarkers in Gastrointestinal Malignancies: AProspective Observational Study - Dr.Rajandeep Singh Bali, Dr.Balaji Rajendran, Dr. Shakeel Ahmed Mir, Dr.Rizwan Ahmad, Dr.Aijaz ahmad (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Gastrointestinal (GI) malignancies are among the leading causes of cancer-relatedmorbidity and mortality worldwide. Conventional staging systems remain the cornerstone of prognostication, but they often fail to capture